2009
DOI: 10.1111/j.1365-2389.2008.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition in soil and chemical changes of maize roots with genetic variations affecting cell wall quality

Abstract: Roots of brown-midrib (F2bm1 and F292bm3) maize mutants and their normal isogenic counterparts (F2 and F292) were used to evaluate the changes in chemical cell wall features with regard to polysaccharides, lignin composition and interconnecting phenolic acids during root degradation in soil. To this end, the chemical variability of roots of brown-midrib mutants and their normal counterparts was compared and its subsequent impact on carbon (C) mineralization determined under controlled conditions. The bm1 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 33 publications
(41 reference statements)
1
57
0
Order By: Relevance
“…In these systems, lignin structures can be modified by altering the expression of genes coding for enzymes in the lignin biosynthesis pathway, or by chemically modifying the lignin as it polymerizes in the cell wall. Previous studies have used genetically or chemically modified plant systems in laboratory studies to examine lignin chemistry effects on cell wall degradation by rumen microbes (Grabber 2005;Grabber et al 2009;Jung and Casler 1991;Jung and Buxton 1994;Jung et al 1999;Vailhe et al 1996), extracellular enzyme preparations (Grabber 2005;Grabber et al 1998c;Grabber et al 1997;Li et al 2010), or microbes in soil microcosms (Hénault et al 2006;Machinet et al 2009;Webster et al 2005). These studies have found mixed evidence for the hypothesis that lignin chemical composition affects plant cell wall degradation.…”
Section: Introductionmentioning
confidence: 97%
“…In these systems, lignin structures can be modified by altering the expression of genes coding for enzymes in the lignin biosynthesis pathway, or by chemically modifying the lignin as it polymerizes in the cell wall. Previous studies have used genetically or chemically modified plant systems in laboratory studies to examine lignin chemistry effects on cell wall degradation by rumen microbes (Grabber 2005;Grabber et al 2009;Jung and Casler 1991;Jung and Buxton 1994;Jung et al 1999;Vailhe et al 1996), extracellular enzyme preparations (Grabber 2005;Grabber et al 1998c;Grabber et al 1997;Li et al 2010), or microbes in soil microcosms (Hénault et al 2006;Machinet et al 2009;Webster et al 2005). These studies have found mixed evidence for the hypothesis that lignin chemical composition affects plant cell wall degradation.…”
Section: Introductionmentioning
confidence: 97%
“…Incubation was performed under controlled conditions. The soil used in these experiments, sampled from the 0-10 cm layer at the INRA experimental station in northern France (49°80′N, 3°6 0′E), was a silty loam comprised of 17.8 % clay, 77.3 % silt, 3.8 % sand, and 0.95 % organic C, with a pH H2O of 7.6 (Machinet et al 2009). The moist soil was sieved through a 2-mm mesh-size sieve and stored at 4°C until the initiation of incubation.…”
Section: Experimental Design For Decomposition Incubationmentioning
confidence: 99%
“…Chemical characteristics of decomposing leaves and roots were expressed in relation to the initial dry matter (non-decomposed dry matter, ND-DM) by taking into account the loss of mass by decomposition, calculated from the cumulative amounts of mineralized C (Machinet et al 2009). These chemical analyses were performed on only two replicates at each date, as previous experiments demonstrated extremely low variation in similar results (Bertrand et al 2006;Machinet et al 2009Machinet et al , 2011a. This low number of replicates decreased the power of statistical analyses so that significant results should be viewed as conservative.…”
Section: Data Treatment and Analysismentioning
confidence: 99%
“…These arabinose substitutions can be esterified by ferulic acid (FA) and form diferulate bridges and ether linkages with lignin, thereby crosslinking arabinoxylan chains and arabinoxylan/lignin connections, respectively. The presence of lignin and cross-linking phenolic acids is well known to regulate enzyme access to cellulose and hemicelluloses in forage digestibility and bioreffinery studies (Chesson 1988(Chesson , 1997Lam et al 2003;Berlin et al 2006) and appears to affect decomposition in soils (Machinet et al 2009(Machinet et al , 2011aTalbot et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation